Pendampingan Pembuatan Game Edukasi dan Animasi Pembelajaran untuk Mereduksi Dampak Negatif TIK dan Meningkatkan Literasi Digital Guru di Kabupaten Maros - Arsyad, Susalti Nur; Zubair, Arie Gunawan Hazairin; SAS, Abdillah; Swandi, Ahmad; Putri, Fina Melani (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2024)
This community service activity aims to improve the quality and creativity of teachers to develop and implement educational games and learning videos/animations that are more interesting and can replace online games that have been widely used by students. With the existence of learning animation videos developed by teachers, misuse of TikTok among students can be minimized. The methods used in this activity include 5 stages, namely socialization, training, technical assistance, technology transfer, and evaluation of the implementation of educational games and learning videos/animations. The results of this activity indicate mastery of counseling materials on limiting the use of games and applications that are not useful on students' smart devices. Overall, this mentoring activity has succeeded in encouraging better technology integration in the educational environment at UPTD SMP Negeri 2 Maros. In addition to producing 41 educational games and 32 learning animations, there has also been an increase in teachers' understanding of the development and implementation of educational games and videos in learning with a value of 0.30 which is in the moderate category.